Effects of riparian buffer width on activity and detection of common bats in the southern Appalachian Mountains - Joy M. O'Keefe; Susan C. Loeb; Patrick D. Gerard; J. Drew Lanham (Wildlife Society Bulletin)
Abstract Riparian zones are important to bats, which use them for foraging, roosting, and drinking. To predict effects of timber harvests in riparian areas on bats, more information is needed on the functional width of riparian zones for bats, and how bats respond to forest removal near small perennial streams. From May to August (2004–2007), we studied bat presence and activity in 1 unharvested site and 3 harvested sites with different riparian‐buffer sizes (0 m, 10 m, and 30 m) in the southern Appalachian Mountains of the United States. We measured activity at 3 distances from the stream in each site (0 m, stream; 23 m, mid; and 46 m, far), classified bat calls by phonic group, and tested the effect of harvest on overall activity, detection, and naïve occupancy rates for 4 phonic groups. Pre‐harvest activity was higher at the far versus stream or mid positions. Position, harvest, and interactions affected post‐harvest change in activity in the treatment sites. Pre‐ and post‐harvest activity was similar at all positions in the 30‐m site. Activity increased significantly in the 0‐m and 10‐m sites, likely due to the presence of edge after harvest. Detection probabilities were higher post‐harvest for larger bats and occupancy of 0‐m and 10‐m sites was higher post‐harvest for all phonic groups except Myotis. Post‐harvest responses suggest that the functional width of riparian zones in our study area is ≥10 m. This study is the first to test the effects of harvesting on use of riparian forests by bats; further long‐term landscape‐scale studies are needed. © 2013 The Wildlife Society.